The Influence of Workload and Stress Work On Employee Performance House Cut Chicken In the village hibiscus Subdistrict Parung - Felix Felinus Laia; Ermalina Ermalina (Citakonsultindo, 2026)
Study This aim For analyze influence burden work and stress Work to performance employees at Home Cut Chicken in Waru Village, District Parung, Bogor Regency. Research This use approach quantitative with design study explanatory. Population in study This is all over employee House Cut Chickens totaling 50 people, with technique taking sample use saturated sampling method so that all over population made into as respondents research. Data collection techniques are carried out through distribution questionnaire that was measured use Likert scale method data analysis used is analysis multiple linear regression with assistance from the Statistical Product and Service Solutions (SPSS) program.Research result show that burden work and stress Work own influence to performance employees. In partial, load Work influential negative and significant to performance employee with mark coefficient regression of -0.319 and the level significance 0.000 < 0.05. Stress work also has an effect negative and significant to performance employee with mark coefficient regression of -0.386 and the level significance 0.000 < 0.05. In simultaneous, load work and stress Work influential significant to performance employees as indicated by the value F count amounting to 37,227 with level significance 0.000 < 0.05. The coefficient value determination (R²) of 0.639 indicates that 63.9% of the variation performance employee can explained by variables burden work and stress work, while the rest influenced by other outside factors study. Research result This show that management burden work and control stress Work become factor important in increase performance employees, especially in the sector production that has demands work tall like House Cut Chicken